Evaluation of cleft lip and palate management in Erbil - Fattah, Jalal Hamasalih; Ali, Humam Sharif (Zanco Journal of Medical Sciences (ZJMS), 2015)
Background and Objectives: Cleft lip and palate are congenital deformities that affect the primary and secondary palates during embryogenesis. The objectives of this study was to record the pattern of presentation of cleft lip and palate in Erbil, the types of surgical procedures, the outcome and complications, hence making recommendations to ensure improved care. Methods: This is a prospective study conducted in Erbil city, in the Department of Plastic Surgery at Rezgary Teaching Hospital and Rapareen Pediatric Hospital from March 2009 to May 2013. A total of 164 patients with cleft lip/palate were included in this study. Statistical package for the social sciences (version 18) was used for data entry and analysis. Results: The age ranged from birth to 24 years. The ratio of male to female was 1.4: 1. The combined cleft lip and palate was the commonest type (87 cases, 53%). The commonest risk factor was poor family (105 cases, 64%), followed by consanguinity (97 cases, 59%). The commonest procedure for cleft lip repair was Millard (67 cases) and that for cleft palate repair was Furlow palatoplasty (57 cases). The commonest complication of cleft lip repair was wide scar (9 cases, 7.5%) mostly below one year of age. Ninety-one percent of the parents were satisfied with the children’s appearance of the lip and 86% of parents were satisfied with palatoplasty result. Conclusion: The high degree of association of consanguinity with the cleft lip and palate emphasizes the importance of education about discouraging consanguineous marriage. Millard repair is still the commonest procedure for cleft lip repair.